1998
DOI: 10.1021/jp9803844
|View full text |Cite
|
Sign up to set email alerts
|

Complexation of Naphthylethanols with β-Cyclodextrin

Abstract: The complexation behavior of 1-naphthyl-1-ethanol (1-NpOH) and 2-naphthyl-1-ethanol (2-NpOH) with β-cyclodextrin (β-CD) was studied by employing several spectroscopic techniques. In the case of 1-NpOH, only a complex with 1:1 stoichiometry is formed with β-CD, which has an equilibrium constant that is smaller than that observed for the 1:1 complex between β-CD and 2-NpOH. Excimer emission was observed in the presence of β-CD for solutions containing high 2-NpOH concentrations. This excimer emission was ascribe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
126
0

Year Published

2000
2000
2011
2011

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 89 publications
(133 citation statements)
references
References 41 publications
7
126
0
Order By: Relevance
“…In this case, interaction with the alcohol shields the BPT guest from the quenching interaction with water, and a very dramatic increase in the S 2 fluorescence results. Hydrogen bonding has also been shown to have significant effects on the properties of triplet states included within CD cavities, using phosphorescence and time-resolved absorbance studies [81][82][83][84][85]. Bohne et al [81][82][83] have shown that triplet xanthone is much more weakly bound in b-CD than is ground-state xanthone, with measured binding constants K of 1100 and 48 M À1 for the ground and triplet states respectively [81].…”
Section: Cyclodextrinsmentioning
confidence: 99%
See 2 more Smart Citations
“…In this case, interaction with the alcohol shields the BPT guest from the quenching interaction with water, and a very dramatic increase in the S 2 fluorescence results. Hydrogen bonding has also been shown to have significant effects on the properties of triplet states included within CD cavities, using phosphorescence and time-resolved absorbance studies [81][82][83][84][85]. Bohne et al [81][82][83] have shown that triplet xanthone is much more weakly bound in b-CD than is ground-state xanthone, with measured binding constants K of 1100 and 48 M À1 for the ground and triplet states respectively [81].…”
Section: Cyclodextrinsmentioning
confidence: 99%
“…Hydrogen bonding has also been shown to have significant effects on the properties of triplet states included within CD cavities, using phosphorescence and time-resolved absorbance studies [81][82][83][84][85]. Bohne et al [81][82][83] have shown that triplet xanthone is much more weakly bound in b-CD than is ground-state xanthone, with measured binding constants K of 1100 and 48 M À1 for the ground and triplet states respectively [81]. They proposed this to be a result of stronger hydrogen bonding abilities of the triplet as compared with the ground state [83], in agreement with the findings described earlier that indicated that increased hydrogen bond abilities of a guest will lead to lower binding [48].…”
Section: Cyclodextrinsmentioning
confidence: 99%
See 1 more Smart Citation
“…The UV detector was operated at 224 nm. For temperature studies, compounds migration times were determined at the temperatures 15,20,25,30,35, and 407C (the precision of each temperature was 60.17C). The electrophoretic system was equilibrated at each temperature for at least 6 h prior to each experiment.…”
Section: Apparatusmentioning
confidence: 99%
“…Their review revealed that both neutral and charged CDs could be exploited in CE to optimize the achiral separations of small molecules and various positional isomers. To elucidate the mechanisms of achiral separation by CDs, spectrophotometric methods and calorimetric titration approaches have been applied to determine the apparent binding constants of guest-CD complexation, as well as the thermodynamic parameters and stoichiometries in the binding of the various positional and structural isomers [16][17][18][19][20].…”
Section: Introductionmentioning
confidence: 99%